Alginate Nanoparticles Containing Cuminum cyminum and Zataria multiflora Essential Oils with Promising Anticancer and Antibacterial Effects - Mahmoud Osanloo; Razieh Ranjbar; Elham Zarenezhad (International Journal of Biomaterials)
Cancer and bacterial infections are major global health concerns driving the need for innovative medicines. This study investigated alginate nanoparticles loaded with essential oils (EOs) from Cuminum cyminum and Zataria multiflora as potential drug delivery systems. The nanoparticles were comprehensively characterized using techniques such as gas chromatography-mass spectrometry (GC-MS), dynamic light scattering (DLS), zetasizer, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and ultraviolet-visible spectroscopy (UV-Vis). Their biological properties against two human skin cancer cell lines (A-375 and A-431) and three bacteria (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus) were also evaluated. Alginate nanoparticles containing C. cyminum and Z. multiflora EOs exhibited sizes of 160 ± 8 nm and 151 ± 10 nm, respectively. Their zeta potentials and encapsulation efficiencies were −18 ± 1 mV and 79 ± 4%, as well as −27 ± 2 mV and 86 ± 5%, respectively. The IC50 values against the tested cell lines and bacteria revealed superior efficacy for nanoparticles containing Z. multiflora EO. Considering the proper efficacy of the proposed nanoparticles, the straightforward preparation method and low cost suggest their potential for further in vivo studies.